Spinal Cord Injury Induced by Gun Shot Wounds: Implications for Occupational Therapy - Rosanne DiZazzo-Miller, DrOT, OTRL, CDP (Scholarworks @ WMU, 2015)
People with spinal cord injuries secondary to gunshot wounds present with many unique occupational challenges in terms of their overall health and well-being, and often live in violent cultures that limit occupational performance. Further awareness and understanding of this subgroup can enable occupational therapists to develop appropriate strategies needed to address the many challenges faced by this population. An in-depth understanding of cultural competence is necessary in the identification, planning, and delivery of appropriate and effective treatment. Further, a case example demonstrates the significant influence occupational therapy can achieve in this area of practice.